Steady-state first-pass perfusion (SSFPP): A new approach to 3D first-pass myocardial perfusion imaging - Giri, Shivraman; Xue, Hui; Maiseyeu, Andrei; Kroeker, Randall; Rajagopalan, Sanjay; White, Richard D.; Zuehlsdorff, Sven; Raman, Subha V.; Simonetti, Orlando P. (Magnetic resonance in medicine, 2014)
Purpose To describe and characterize a new approach to first‐pass myocardial perfusion utilizing balanced steady‐state free precession acquisition without the use of saturation recovery or other magnetization preparation. Theory The balanced steady‐state free precession sequence is inherently sensitive to contrast agent enhancement of the myocardium. This sensitivity can be used to advantage in first‐pass myocardial perfusion imaging by eliminating the need for magnetization preparation. Methods Bloch equation simulations, phantom experiments, and in vivo 2D imaging studies were run comparing the proposed technique with three other methods: saturation recovery spoiled gradient echo, saturation recovery steady‐state free precession, and steady‐state spoiled gradient echo without magnetization preparation. Additionally, an acquisition‐reconstruction strategy for 3D perfusion imaging is proposed and initial experience with this approach is demonstrated in healthy subjects and one patient. Results Phantom experiments verified simulation results showing the sensitivity of the balanced steady‐state free precession sequence to contrast agent enhancement in solid tissue is similar to that of magnetization‐prepared acquisitions. Images acquired in normal volunteers showed the proposed technique provided superior signal and signal‐to‐noise ratio compared with all other sequences at baseline as well as postcontrast. Conclusions A new approach to first‐pass myocardial perfusion is presented that obviates the need for magnetization preparation and provides high signal‐to‐noise ratio. Magn Reson Med 71:133–144, 2014. © 2013 Wiley Periodicals, Inc.